(untitled) (Journal of Forestry, 2025)
The history of pedunculate oak forest regeneration in Croatia can be traced in the following historical order: - Regeneration of virgin forests until 1700. It took place before more intensive settlement to the lowland area of Croatia (Slavonia), while the forests developed completely naturally. Forest regeneration was natural, from seeds, on a small surface area, long-lasting and random. Forests would succeed in places of coordinated abundant crop of acorns and in canopy gaps. - Forest regeneration by incomplete shelterwood felling in the period 1700-1850. The method was used in the period of more intensive settlement and anthropization. Forest regeneration was natural, lasting 10–15 years. It started with preparatory felling on a large area, and ended with final felling on small areas. - Forest regeneration by final felling following five-year ban on driving cattle in the period 1850-1930. This was the period of intensive commercial exploitation of old pedunculate oak forests. Old oak stands aged 200–300 years were regenerated with a small number of oak trees per hectare (20–30). With one final felling of old oak trees, the young growth that appeared during the five-year ban on driving cattle was freed from the shelter. In places where the result of natural regeneration was weak, it was supported by planting acorns. Excessive felling areas, felling of stands with too old and dry-topped trees that yield little or no acorns, the conclusion of harmful contracts that allowed buyers to cut down oak trees first, and the excess of stagnant water in some places were more favorable to the regeneration of pioneer species and weed. - Agro-forestry system in the period 1900-1930. It was introduced in some places where the previous method failed. Weedy forestland was leased for several years for agricultural crops, usually wheat or oats. After the lease had expired, an oak forest was established again by planting acorns. Due to the perceived shortcomings, the method was soon abandoned. When used for agricultural purposes, the soil loses its forest soil properties. The degraded soil is only suitable for pioneer tree species. Pedunculate oak stands planted on degraded soil are of lower quality, vitality and stability compared to those growing on forest soil. - Forest regeneration by the uniform shelterwood method since 1930. It began to be used for the regeneration of stands which are usually managed with rotations of 140 years or, for health reasons, with rotations of 120 or 100 years. This is the standard and most widespread method of regeneration of pedunculate oak forests in Croatia. During the second half of the 20th century, it was modernized with scientific knowledge based on the principles of the Zagreb School of Silviculture. The fellings and the regeneration period are adapted to the forest communities of pedunculate oak. In pedunculate oak forests with hornbeam (As. Carpino betuli-Quercetum roboris /Anić 1959/ emend. Rauš 1969) three fellings are done (preparatory, seeding and final felling). Two fellings (seeding and final felling) and a shorter period of regeneration are used in floodplain oak forests (As. Genisto elatae-Quercetum roboris Ht. 1938). Insufficient natural regeneration is supported according to natural principles, by sowing or planting acorns before the seeding felling. Between 700 and 1000 kg of acorns per hectare are needed for forest regeneration by sowing acorns. For the regeneration of forests by planting of acorns, 400–600 kg are needed. - Regeneration by the conversion of tree mixture since 1980. It is recommended as a close-to-nature method of recovering a degraded site (weedy, waterlogged, polluted, compacted) after the intensive decline of the oak stand. It is carried out by sowing or planting native pioneer tree species: narrow-leaved ash, black alder, poplar and willow. The newly created pioneer forest has the task of biologically preparing the degraded soil for the return of the pedunculate oak. - Forest regeneration by the strip and group shelterwood method since 1990. It is recommended in conditions of weak, irregular and uneven acorn harvest, and the emphasized need to protect nature and the environment. It is one of the ways of adapting forest regeneration to climate changes and natural disasters. The common denominator of methods of regeneration of the oak forests in Croatia is natural or close to nature regeneration under the shelter of mature trees. This way of forming pedunculate oak forests is an important historical feature of forest management, and the main reason for their great naturalness. The introduction of the principles of the Zagreb School of Silviculture into the practice of forest regeneration in the first half of the 20th century directly contributed to the preservation of the high naturalness and quality of the pedunculate oak forests as follows: natural regeneration under the shelter of mature trees; the creation of mixed stands of pedunculate oak with companions from the natural forest community; and supporting natural regeneration by sowing or planting acorns under the shelter of mature trees. Forest regeneration by the strip and group shelterwood method is optimal in the present ecological conditions. Large stands (5-60 ha) of regular spatial shapes can be regenerated by shelterwood felling in the form of stripes and circles with a width of 2-4 stand height and an area of 1-5 ha. Small (1-3 ha) and medium-sized (3-5 ha) stands with irregular spatial shapes can be regenerated by irregular shelterwood method. Regrowth cores can have a width of 1-2 stand height and an area of 0.01-0.02 ha.